After dental instruments have been sterilised unwrapped and are dry, is enclosure in lidded trays, suitable bags or containers (compared with immediate use or loose storage) sufficient to protect them from microbial recontamination relevant to patient safety outcomes?. (2017) - Unknown
No abstract available